The physical impact of towed demersal fishing gears on soft sediments. (18th August 2015) - O'Neill, F. G.; Ivanović, A.
Abstract: An improved understanding of the physical interaction of towed demersal fishing gears with the seabed has been developed in recent years, and there is a clearer view of the underpinning mechanical processes that lead to the modification and alteration of the benthic environment. The physical impact of these gears on soft sediments can be classified broadly as being either geotechnical or hydrodynamic in nature: penetration and piercing of the substrate, lateral displacement of sediment, and the influence of the pressure field transmitted through the sediment can be considered geotechnical, whereas the mobilization of sediment into the water column can be considered hydrodynamic. A number of experimental and numerical approaches have been used to gain better insights of these physical processes. These include small-scale modelling in towing tanks and sand channels; large-scale modelling in the field; measurements behind full-scale towed gears at sea; numerical/mathematical modelling of sediment mechanics; and numerical/mathematical modelling of hydrodynamics. Here, we will review this research, and that in associated fields, and show how it can form the basis of predictive models of the benthic impact of trawl gears.